Tinjauan Awal Kritisisme Immanuel Kant - Tarman, Al-Faiz Muhammad Rabbany; Suherman, Eman (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2024)
This research is motivated by Immanuel Kant's thoughts regarding his efforts to reconcile the conflict between rationalism and empiricism. The purpose of this research is to synthesize the two schools of philosophy: rationalism and empiricism through Immanuel Kant's critical thinking. This research uses a qualitative method with a library research approach. The results of this study indicate that the acquisition of knowledge is a synthesis of the two elements, namely a priori and a posteriori. These two elements are closely related, correlated, both provide an important role as the basis of knowledge. Thus, between the thoughts of ratioanalism and empiricism, both are elements that play an important role that cannot be separated.